2014
DOI: 10.1037/pas0000012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of contextual information on lay judgments of childhood mental health concerns.

Abstract: Decisions about whether a person is in need of mental health care are often made by laypeople with no training in the identification of mental health concerns. For example, the parent of a child displaying problematic behavior has to decide whether this behavior is likely related to mental health concerns and necessitates professional care. The process of identifying mental health concerns is made more complicated by the rich background of real-world environmental factors or contexts in which concerns can pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 40 publications
2
29
1
Order By: Relevance
“…For instance, whereas high-risk contextual information might have influenced one clinician's judgments about a child's truancy, the same high-risk contextual information might have had little influence on another clinician's judgments about the child's truancy. These findings have since been replicated when examining judgments about attention-deficit/hyperactivity concerns, as well as judgments completed by laypeople (Marsh, De Los Reyes, & Wallerstein, 2014). …”
Section: Conceptual Foundations Of Multi-informant Mental Health Assementioning
confidence: 77%
“…For instance, whereas high-risk contextual information might have influenced one clinician's judgments about a child's truancy, the same high-risk contextual information might have had little influence on another clinician's judgments about the child's truancy. These findings have since been replicated when examining judgments about attention-deficit/hyperactivity concerns, as well as judgments completed by laypeople (Marsh, De Los Reyes, & Wallerstein, 2014). …”
Section: Conceptual Foundations Of Multi-informant Mental Health Assementioning
confidence: 77%
“…As family members are normally the gateway to engagement of their children in treatment, future studies might explore the influence of context on their judgments of treatment effectiveness. For judgments of the existence of mental disorder, research has demonstrated that laypersons often make similar distinctions as professionals (Wakefield et al 2006;Garb 1998;Marsh et al 2014), and some scholars think that the similarities may reflect general reasoning processes (Marsh et al 2014). From these findings, we expect that parents may be equally sensitive to the importance of context for making judgments about treatment.…”
Section: Iqr Interquartile Rangementioning
confidence: 89%
“…In this paper we explore this issue by including a sample of laypeople and assessing what beliefs underlie their use of contextual information in making a diagnostic judgment. This is an important issue to address because laypeople comprise key stakeholders in determining whether their own behavior or that of significant others (e.g., children, spouses, or coworkers) warrants mental health care (e.g., they are the point of initial contact between a person needing care and a mental health professional; see Marsh et al, 2014).…”
Section: The Influence Of Beliefs On Clinical Judgmentsmentioning
confidence: 99%
“…In the following experiment, we tested whether the perceived prevalence, diagnosticity, abnormal-ity, or importance to diagnosis of mental disorder symptoms predicts the extent to which judges are influenced by contextual life information in making clinical ratings of those symptoms. To do this we adopt the methodology of De Los Reyes and Marsh (2011) and Marsh et al (2014) and test symptoms within conduct disorder. We predict the influence of context will follow a curvilinear relationship as a function of our measures of interest, with symptoms that are seen as the most and least possessing of a given construct (i.e., prevalence, diagnosticity, abnormality, or importance) lending the same information to diagnosis regardless of context.…”
Section: The Influence Of Beliefs On Clinical Judgmentsmentioning
confidence: 99%
See 1 more Smart Citation